The Surprising Breadth of Post-Grant Review for Covered-Business-Method Patents - Riley, Andrew; Stroud, Jonathan; Totten, Jeffrey (Science and Technology Law Review, 2014)
Sued for or threatened with infringement? Companies and innovators sued for infringement over software, Internet, or business-method patents have a new means for quick and relatively low-cost resolution. By using the recently enacted post-grant review procedures at the U.S. Patent and Trademark Office created by the America Invents Act and implemented September 16, 2012, parties can resolve software disputes quickly and relatively cheaply, compared to the rigors of a full trial. While there are never easy answers, these reviews enable many parties not only to lower costs but also to protect their own often-nascent software innovations from predatory suit.